GREEN TOURISM MARKETING FOR SUSTAINABLE DEVELOPMENT ENVIRONMENT - Ganjar Ndaru Ikhtiagung; Sari Widya Utami (Jurnal Pariwisata Pesona, 2020)
This study was conducted at Payau Mangrove Forest Tourism in Cilacap Regency KelurahanTritihkulon. The reason for the selection of the site because the object of this research has occurred changes in mangrove forest function to be a tourism place with its management has not been insightful in the environment. The concept of building regional tourism, especially in Cilacap Regency, must be based on sustainable development. This means that through green tourism marketing in the tourism development efforts in forest brackish mangrove in the village Tritih Kulon is an integrated and organized effort to develop the quality of life by regulating the provision, development, Sustainable utilization and maintenance of resources. However, it can be implemented if the good governance system that involves the active and balanced participation between the Government, education, business people, media, and society. This research is a qualitative-exploratory study that emphasizes the enrichment aspect in the field of research strength. But in this study not only came to describe the problem only, but the research will come to the stage of drafting the development model, and applicative by conducting observations and evaluation in the field so that the data Obtained will be done mapping and identification with SWOT analysis approach. SWOT analysis results Demonstrate the strategy used is SO (strength to opportunities) namely by optimizing the whole power and make use of all opportunities in the forest tourism Payau Mangrove.